A novel structural design of air cathodes expanding three-phase reaction interfaces for zinc-air batteries. (15th May 2021) - Pan, Lyuming; Chen, Dongfang; Pei, Pucheng; Huang, Shangwei; Ren, Peng; Song, Xin
Graphical abstract: Highlights: The three-phase reaction interfaces expand from 2D plane to 3D zone. The power density increases by using novel structure. A peak power density of 120 mW·cm −2 for zinc-air battery is achieved. Performance decay of air cathodes isn't obvious after continuous discharging. Abstract: Zinc-air batteries are considered as potential energy conversion systems. One of the main issues of zinc-air batteries is the low actual power density. However, the three-phase reaction interfaces are limited in 2D plane of conventional air cathodes, which limits the electrochemical kinetics and the commercialization of zinc-air batteries. Here, a novel structural design of air cathodes with multi current collectors and gradient hydrophobicity to improve the discharge power for zinc-air batteries is proposed. Based on non-noble metal catalysts, the three-phase reaction interfaces expand from 2D plane to 3D zone by the novel structural design, increasing the power density of the battery. The gradient distribution of hydrophobicity in the air cathode can be obtained in one step through the soaking-drying process. When the soaking-drying process reaches twice, the optimal performance is achieved due to the balance of hydrophilicity and hydrophobicity. The peak power density of 120 mW·cm −2 is achieved in the zinc-air battery with MnO2 as catalysts. After continuously discharging at 20 mA·cm −2 exceed 9 h, the electrochemical performance can be restored by replacing with a new metal anode and keeping the initial air cathode. This work illustrates that the novel structural design of air cathodes can effectively improve the power density of zinc-air batteries, which is beneficial to the application of zinc-air batteries in the fields of energy storage and conversion.